Support Functionalization with a Phosphine‐Containing Hyperbranched Polymer: A Strategy to Enhance Phosphine Grafting and Metal Loading in a Hydroformylation Catalyst. Issue 11 (12th May 2016) - Garcia, Marco A. S.; Heyder, Rodrigo S.; Oliveira, Kelley C. B.; Costa, Jean C. S.; Corio, Paola; Gusevskaya, Elena V.; dos Santos, Eduardo N.; Bazito, Reinaldo C.; Rossi, Liane M.
Abstract: We present the design of a hydroformylation catalyst through the immobilization of air‐stable Rh nanoparticles (NPs) on a magnetic support functionalized with a hyperbranched polymer that bears terminal phosphine groups. The catalyst modification with the hyperbranched polymer improved the metal–support interaction, the metal loading, and the catalytic activity. The catalyst was active for the hydroformylation of natural products, such as estragole, and could be used in successive reactions with negligible metal leaching. The phosphine grafting played a key role in the recyclability of Rh NPs under hydroformylation conditions. The catalytic activity was maintained in successive reactions, even if the catalyst was exposed to air during each recovery procedure. The modification of the support with hyperbranched polyester allowed us either to increase the number of Rh active species or to obtain more active Rh species on the catalyst surface. Abstract : Rely on the polymer ! The heterogenization of a rhodium catalyst onto a magnetic support modified with a polyester hyperbranched polymer with pendant diphenylphosphine moieties allows the preparation of a very active hydroformylation catalyst and its easy recovery without loss of metal, reactivity, or selectivity.